PENERJEMAHAN AIZUCHI PADA ANIME ICHIGO MARSHMALLOW - Martines, Dian; Aibonotika, Arza; Budiani, Dini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Absrtact: This study examines the use of Aizuchi in the Ichigo Marshmallow anime. The formulation of the problem analyzed includes the functions and types of aizuchi used in conversations in the Ichigo Marshmallow anime, and examines the equivalence of aizuchi translation in Marshmallow anime. The translation methods used for this research are free translation methods and adaptation translation methods. The results found from the research are after watching the anime Ichigo Marshmallow episodes 1-5, there are 93 words of aizuchi. The most common form of aizuchi is 86 words aizuchishi, and the most functions found are hearing or kiite iru to iu shingou as many as 53 words. The translation methods used by translators are free translation methods and adaptation translation methods. Translators use both methods because both methods produce the translation that is most equivalent to Indonesian. The most frequently occurring translation procedures are the equivalency procedure, the borrowing procedure, and the transposition procedure.Key Words: Aizuchi, Sentence Conversation, the equivalence of translation